Storage of minimally processed 'Cantaloupe' melons with edible coatings (Research, Society and Development, 2020)
The present work aimed to evaluate the quality of minimally processed 'Cantaloupe' melons submitted to edible coatings, based on chitosan and yam starch during refrigerated storage. The melons were submitted to six treatments: Treatment 1 (without coating), Treatment 2 (Calcium Chloride 1%, without coating), Treatment 3 (Chitosan 1% + Glycerol 2%), Treatment 4 (Calcium Chloride 1% + Chitosan 1% + Glycerol 2%), Treatment 5 (Yam starch 2% + Glycerol 2%) and Treatment 6 (Calcium Chloride 1% + Yam starch 2% + Glycerol 2%). The treated melons were stored at 3 ± 2ºC and 75 ± 4% RH and the physicochemical and bioactive compounds evaluations were carried out over 12 days (0, 2, 4, 6, 8, 10, and 12 days). The high loss of mass in melons from the control treatments (T1) and calcium chloride 1% + chitosan 1% (T4) limited the shelf life of the fruits. Melons treated with 2% yam starch (T5) and 1% calcium chloride + 2% yam starch (T6) associated with refrigeration preserved the quality and integrity of the fruits until the 8th day of storage, with higher levels of bioactive compounds such as carotenoids, extractable polyphenols, and ascorbic acid.